POTENSI EKSTRAK DAUN SIRIH (Piper betle liin) SEBAGAI BIOFUNGISIDA PENYAKIT BUSUK BUAH STROBERI (Colletotrichum fragariae brooks) SECARA IN-VITRO - Ariyanti, Eka Lestari; Jahuddin, Rahmat; Yunus, Muhammad (Jurnal Agroteknos, 2012)
One of important pathogens on strawberry is Colletotrichum fragariae causing fruit rot. The study aimed to investigate the potency of water betel leaf extract (Piper betle liin) as biofungicides for inhibiting growth of C. Fragariae under in-vitro test. The study was arranged in Completely Randomized Design that consisted of five treatments : 0%, 10%, 20%, 30%, and 40% concentration of water betel leaf extract. Betel leaf was extracted by grinded in mortal, added steril water and mixed with PDA medium. The study showed that the 40% concentration of water betel leaf axtraction was most effective to inhibit growth of C. Fragariae in-vitro on PDA medium. The inhibiting ability of coloni grown was 58,57%, while inhibiting of spore germination was 33,59%. Key word : Colletotrichum fragariae, strawberry, water betel leaf extract.